2018
DOI: 10.1159/000494888
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Maternal Plasma Concentrations of Retinol-Binding Protein 4 and Risk of Gestational Diabetes Mellitus

Abstract: Background: The aim of this study was to investigate whether retinol-binding protein 4 (RBP4) concentrations, measured at the first prenatal visit, are associated with risk of gestational diabetes mellitus (GDM). Methods: From July 2015 to June 2016, consecutive women who admitted to the obstetrics center of our hospital were included. At the first prenatal visit (the median gestational age was 6 [interquartile range 4–10] weeks) in the hospital, involved subjects were tested for fasting plasma glucose (FPG) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 45 publications
0
25
2
Order By: Relevance
“…Interestingly, high levels of FABP4 were proposed as a predictive biomarker of GDM from at the 1st and 3rd trimester of gestation [133135]. Also, an upregulation of plasma RBP4 at the 1st and 2nd trimester was modestly correlated with GDM risk, particularly among women with advanced age and obesity [115, 136] (Table 3A). Finally, fibroblast growth factor-23 (FGF-23) is as a multi-functional cytokine with relevant implications in phosphate and vitamin-D metabolism.…”
Section: Prospective Diagnostic and Predictive Markers For Gdm With Amentioning
confidence: 99%
“…Interestingly, high levels of FABP4 were proposed as a predictive biomarker of GDM from at the 1st and 3rd trimester of gestation [133135]. Also, an upregulation of plasma RBP4 at the 1st and 2nd trimester was modestly correlated with GDM risk, particularly among women with advanced age and obesity [115, 136] (Table 3A). Finally, fibroblast growth factor-23 (FGF-23) is as a multi-functional cytokine with relevant implications in phosphate and vitamin-D metabolism.…”
Section: Prospective Diagnostic and Predictive Markers For Gdm With Amentioning
confidence: 99%
“…Among diabetic pregnancies, the adipokine RBP does not have a statistically significant association with the occurrence of PE ( 92 ). Other studies have investigated the association between higher RBP concentrations and the risk of gestational diabetes, finding both positive ( 93–96 ) and negative associations ( 97 ).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between RBP4 levels in early pregnancy and the risk of GDM have been assessed by limited studies and inconclusive results were yielded. A prospective study found that compared with the first quartile of RBP4 in the first trimester, adjusted ORs of GDM for the second, third and fourth quartile were 1.54, 3.05 and 6.36 respectively [7]. Another case-control study found participants in the highest quartile of serum RBP4 had a 1.89 times higher risk of GDM compared with participants in the lowest quartile, while the relationship did not reach statistical significance after adjustment for maternal age, race, family history of diabetes, and pre-pregnancy overweight status [21].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this metaanalysis only includes one article in the "before 24 weeks" subgroup and no association between serum RBP4 level and GDM risk was found [9]. Recently, a prospective study revealed that early pregnancy RBP4 concentrations were associated with increased risk of GDM [7]. However, none of the previous studies analyzed RBP4 levels at different trimesters before the diagnosis of GDM.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation